Outcomes after orthopedic trauma - Michael Suk; Monica Daigl; Richard E Buckley; Dean G Lorich; David L Helfet; Beate Hanson (Journal of Orthopaedic Surgery, 2017)
Background: Clinical orthopedic research needs better ability to assess patient expectations with regard to orthopedic trauma surgery outcomes. The aim of this study was to investigate to which extent patient expectations prior to surgery could be met after surgery. Methods: Patients (≥18 years) with surgical ankle fractures were prospectively recruited at 5 orthopedic trauma clinics in the United States (USA), Canada, and Brazil and followed up for 12 months. Patients were asked to complete a previously validated trauma expectation factor (TEF) questionnaire prior to surgery and a trauma outcome measure (TOM) 1 year after surgery. Results: At 1 year, 155 patients had provided complete records. Almost half (49%; 76/155) had a 1-year TOM score equaling or exceeding their preoperative TEF score (95% CI: 41–57%). The remaining scores failed to meet patient expectations. TOM scores matched or exceeded patient expectations for 33% of patients in the USA and 47% in Canada, but for 69% in Brazil ( p = 0.001 (USA); p = 0.024 (Canada)). This geographical effect was attributable to higher patient expectations in North America as compared to Brazil (average TEF scores: 36 (North America) versus 31 (Brazil); p < 0.001). Patients with lower household income or smokers were more likely to be satisfied with their treatment ( p = 0.02 and p = 0.05, respectively). Furthermore, patients with severe type C fractures had better rates of satisfaction (62%) than patients with simpler B (50%) or type A fractures (33%) ( p = 0.01 [C type versus A type]). Conclusions: Orthopedic surgeons have difficulty in meeting or exceeding presurgical patient expectations of long-term outcomes for ankle fracture surgery. This study provides evidence that culture, geography, and surgeon—patient communication have considerable influence on patient expectations.